The Role of Community Empowerment and Social Innovation in Enhancing Village Economic Self-Reliance through Community Service Programs - Sunarso, Budi; Nur, Muhammad; Kristanti, Desi (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
Sustainable rural development requires an approach that is not only oriented toward economic growth but also toward strengthening community capacity and self-reliance. This study aims to expand and enrich the body of scholarly references on community service by examining the role of community empowerment and social innovation in enhancing village economic self-reliance. The study employs a literature review method with a qualitative approach and descriptive analysis. Data were collected from scholarly articles sourced from Google Scholar and credible websites published between 1997 and 2025. Of the 50 articles identified in the initial stage, a rigorous selection process resulted in 27 relevant articles for analysis. The findings indicate that community empowerment based on active community participation, supported by contextual social innovation, contributes significantly to improving village economic self-reliance. Community service programs implemented in a collaborative and sustainable manner have been shown to strengthen local economic capacity, increase community income, and reinforce village institutions. This study concludes that the integration of community empowerment and social innovation constitutes a key strategy in community service efforts to achieve sustainable village economic self-reliance.